The general anesthesia experience of deletion 8p syndrome patient -A case report- - Woo Jong Shin; Sang Duk Kim; Kyoung Hun Kim (Korean Journal of Anesthesiology, 2011)
A deletion 8p syndrome is a relatively uncommon congenital disease characterized by mental retardation associated with multiple malformation that make anesthetic management a challenge. Anesthetic management of a patient with deletion 8p syndrome may pose a serious problem mainly from difficult tracheal intubation, aspiration complication and cardiac malformation. We experienced a case of 10 year-old boy with a deletion 8p syndrome who underwent appendectomy under the general anesthesia. Intubation was performed by video glidescope after unsuccessful attempt with Macintosh laryngoscope. A high arched palate, short neck, poor patient cooperation due to mental retardation and occasional autistic behaviour made airway management difficult. This case should alert anesthesiologists to the greater difficulties of managing patients with deletion 8p syndrome.